Memorizing Vocabulary through Mind Mapping Technique - Munsakorn, Nuttanuch (Mediterranean Journal of Social Sciences, 2012)
This paper makes an attempt to show the effectiveness of mind mapping technique as a vocabulary storage method.The study was a one-group pretest-posttest experiment and aimed to investigate the effect of mind mapping technique onvocabularies learning of 40 Bangkok University students and explore their attitude towards the use of mind mapping technique.The instruments were the vocabulary tests, and the questionnaire exploring attitude towards mind mapping technique. Thepretest and posttest scores of the experimental group were calculated for descriptive statistics and compared using a dependentt-Test measure. It was found that students obtained higher scores for the posttest than the pretest scores at the 0.05 level ofsignificance. In addition, their attitude towards using the mind mapping technique was at a high level. Moreover, the results fromthis study supported that using mind mapping technique helped the students store a new bunch of vocabularies, and motivatedthem to learn English language.